2019
DOI: 10.7150/jca.33431
|View full text |Cite
|
Sign up to set email alerts
|

Association between Polymorphisms of Vitamin D Receptor and Lung Cancer Susceptibility: Evidence from an Updated Meta-analysis

Abstract: Purpose: The aim of this meta-analysis was to investigate polymorphism of Bsm1, Apal, Taq1 and Cdx-2 in vitamin D receptor (VDR) associations in relation to lung cancer (LC) susceptibility. Methods: 9 literatures were recruited into this meta-analysis from PubMed, PMC, Embase, Web of Science, Cochrane library and CNKI. STATA version 15.1 was used for statistical tests. The heterogeneity was tested using I 2 statistics. According to the value of I 2 , the random-effect model (REM) or fixed-effect model (FEM) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…The results showed that Bsm1 and Cdx2 polymorphisms were protective factors for avoiding lung cancer incidence, while T allele and TT genotype of Taq1 were risk factors for lung cancer susceptibility. Our results were partly consistent with previous meta-analysis studies conducted by Yu et al (2018), which indicated that the Bsm1 A allele was negatively related to the lung cancer risk and the T allele carriers were at increased risk of lung cancer, and by Li et al (2019), which suggested that Bsm1, Taq1, and Cdx-2 polymorphisms may contribute to lung cancer susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that Bsm1 and Cdx2 polymorphisms were protective factors for avoiding lung cancer incidence, while T allele and TT genotype of Taq1 were risk factors for lung cancer susceptibility. Our results were partly consistent with previous meta-analysis studies conducted by Yu et al (2018), which indicated that the Bsm1 A allele was negatively related to the lung cancer risk and the T allele carriers were at increased risk of lung cancer, and by Li et al (2019), which suggested that Bsm1, Taq1, and Cdx-2 polymorphisms may contribute to lung cancer susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have found a relationship between VDR gene polymorphisms and the risk of various cancers [30,35,46]. Also, we have previously demonstrated an association between RET gene polymorphisms and the risk of medullary thyroid cancer [18].…”
Section: Abstract Medullary Thyroid Carcinoma Vitamin D Vitamin D Receptor Polymorphism Introductionsupporting
confidence: 62%
“…Previous studies have revealed that vitamin d, which can be hydroxylated to the active form 1,25(oH) 2 d3 (referred to as vitamin d or d3 in the present study), activates Vdr (9,10). Furthermore, Vdr expression is associated with cancer risk and mortality in various types of cancer, including breast, lung and colorectal cancer (11)(12)(13)(14). other studies suggested that the vitamin d and Vdr complex binds to p21 and p27 proteins, which suppress dna synthesis, inactivate mitogenic signals and inhibit tumor progression (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 65%